ENDOTHELIAL ADHESIVE FUNCTION IN PATIENTS WITH ISCHEMIC HEART DISEASE COMPLICATED BY CHRONIC HEART FAILURE AND ATRIAL FIBRILLATION - A. N. Zakirova; E. R. Abdukova; N. E. Zakirova (Столичная издательская компания, 2015)
Aim. To access the role of endothelial adhesive dysfunction in the development of atrial fibrillation (AF) in patients with ischemic heart disease (IHD) complicated by chronic heart failure (CHF). Material and methods. 111 patients with CHF class I-IV due to myocardial ischemia were included in the study. All participants were divided into four groups according to the presence of AF and CHF class. The control group consisted of 25 healthy individuals. Endothelial adhesive function was assessed by levels of soluble intercellular adhesive molecules sVCAM-1 and sE-selectin. Results. The sVCAM-1 level in patients with CHF class III-IV with AF was significantly higher than this in control group and patients with CHF class I-II regardless of AF occurrence, as well as higher than this in patients with CHF class III-IV without AF (65%, 56.1%, 36.3% and 13.9%, respectively, p<0.05). Direct correlations between sVCAM-1 level and the left atrium volume index (LAVI) (r=0.52; p<0.05) and between sE-selectin level and LAVI (r=0.48; p<0.05) were revealed. Conclusion. Endothelial adhesive dysfunction associates with AF existence and the severity of CHF.